ENGLISH LEARNING EDUCATIONAL GAMES FOR HEARING AND SPEECH IMPAIRMENT STUDENTS AT SLB B YAKUT PURWOKERTO - Yogiek Indra Kurniawan; Uki Hares Yulianti; Nadia Gitya Yulianita; Andika Putra Pratama (Jurnal Teknik Informatika (Jutif), 2022)
Students with hearing and speech impairment at the Special School for the Hearing and Speech Impairment (SLB B) Yakut Purwokerto do not have high level of interest in learning. Moreover, the use of manual learning media which are based on books and blackboards also causes a lack of students’ understanding. This research aims to develop an alternative learning media which are based on educational games to learn English for students with hearing and speech impairment at SLB-B Yakut Purwokerto with the name "Matching" (Match a Thing). The research method in developing this game was the Multimedia Development Life Cycle which consisted of six stages, namely Concept, Design, Assets / Materials Collecting, Manufacturing (assembly), Testing, and Release (distribution). This educational game was built using the Construct 2 game engine and could be accessed using a web browser. The result of this research is an English-learning-educational game that has several menus, including Main Menu, Help, Play, Library, and Evaluation/Quiz. Based on a blackbox testing, valid results were obtained for all given test scenarios, therefore this game is in accordance with the application developer’s expectations. In addition, based on the User Acceptance Testing (UAT), the average perception result was 89% with an indicator of the "Very Good" category which indicates that this application is feasible to use in the English learning process.